Musadoc 2002 - International Network for the Improvement of Banana and Plantain (2002)
The up-to-date versions of the INIBAP databases, MUSALIT - containing abstracts and bibliographic records of publications on Musa, and BRIS - the database of banana researchers are available. As are all of the recent publications, including Strategy for the global Musa, new factsheets and publications from 2002, such as the 2001 Annual Report.